Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov. - Tavares, Carolina; Gusmão, Jaqueline (Zootaxa, 2016)
The pink shrimp, Farfantepenaeus subtilis, actually comprises two cryptic species confused under a single name. Despite morphological and molecular evidences accumulated since 1967, the new species confused with F. subtilis has never been formally described. In this paper, Farfantepenaeus isabelae sp. nov., is described and compared to its close relatives, F. brasiliensis, F. notialis, F. paulensis and F. subtilis s. str..